A STUDY ON THE IMAGE NARRATIVE ISSUES IN ANIMATION NARRATIVE OF NOVICE ANIMATORS’ ANIMATION - A CASE STUDY OF THE SHORTLISTED SHORT FILMS IN THE 2019 TAINAN ANIMATION AGE FESTIVAL - Lee, Ya-Hsueh; Zhang, Yu-Yun (PEOPLE: International Journal of Social Sciences, 2024)
The best animation depends on the image narrative and the use of the lens. In order to connect between the animation and the audience, both skills are significant and professional. General animation narrative requires that the story content be complete, have a beginning and an end, and pay attention to cause and effect. Through the structure of the beginning and development, the story can be advanced step by step. However, it’s important and challenging for novice animators to both deliver scientific knowledge and storytelling in a short. Whether it is the timing of the shot, the misplacement of the character's position, unclear vocabulary, unclear movements, or expressions, etc., many factors may cause the audience to not understand. Therefore, given this situation, this study collected 6 animations which were made by students from the 2019 Tainan Animation Age Festival and then found out the common problems with novice animators by conducting participant observation and case study research. The result demonstrates the more common problem for novice animators is the animated image narrative, such as insufficient frames, unclear expression of character movements and expressions, unclear use of lenses, etc. This result can be a reference for novice animators or beginners.